PENGARUH NPL, CAR, ROA DAN BI RATE TERHADAP PENYALURAN KREDIT PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014 – 2016 - Eling Ri Kurniati; Febriana Eriska Putri (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2020)
The problem on this research was the number of internal and external factors of the bank that affect lending to commercial banks.This research aimed to analyze the effect of partial Non Performing Loans (NPL), Capital Eduquecy Ratio (CAR), Return On Assets (ROA) and BI Rate on lending to commercial banks, and analyze the influence of Non Performing Loan (NPL) variables, Capital Eduquecy Ratio (CAR), Return On Assets (ROA) and BI Rate simultaneously to lending to commercial banks. This research was associative causal. The data used in this research was secondary data from the results of Bank Indonesia publications and the official IDX website at www.idx.co.id. The population on this research were all publicly traded public banks listed on the IDX. The sampling technique in this research used purposive sampling method. The total sample in this research were 25 banks. Data Analysis in this research using multiple linear regression analysis with SPSS software. The results showed that the partial Non Performing Loans (NPL), Capital Eduquecy Ratio (CAR), and BI Rate did not affect credit distribution while the Return on Assets (ROA) variable partially affected the lending. Simultaneously the Non Performing Loan variable (NPL), Capital Eduquecy Ratio (CAR), Return On Assets (ROA) and the BI Rate have an effect on lending.